Immune gene expression in gilthead seabream (Sparus aurata) after Lymphocystis disease virus (LCDV‐Sa) challenge resulting in asymptomatic infection - Leiva Rebollo, Rocío; Labella Vera, Alejandro Manuel; Borrego-García, Juan José; Castro-López, María Dolores (Oxford Academic, 2020)
Aims: To determine the immune gene expression response of gilthead seabream (Sparus aurata) that is experimentally infected with the lymphocystivirus LCDV-Sa. Methods and Results: Viral DNA and transcripts were detected by qPCR in all samples from fish injected with LCDV-Sa, demonstrating that the virus establish a systemic and asymptomatic infection. The expression of 23 immune-related genes was also analysed by RT-qPCR in the head kidney (HK) and intestine at several times post-infection (dpi). In HK, the expression of five type I interferon (IFN)-related genes (ifn, irf3, mx2, mx3 and isg15), il10 and ck10 was upregulated at 1–3 dpi, while genes related to the inflammation process (tnfa, il1ß, il6, casp1) were not differentially expressed or even downregulated. The expression profile in the intestine was different regarding type I INF-related genes. An upregulated c3 and ighm expression was observed in both HK and intestine at 3–8 dpi. Finally, the transcription of nccrp1 and mhcIIa was induced in HK, whereas tcrb expression was downregulated in both organs. Conclusions: LCDV-Sa seems to trigger an immune response in gilthead seabream characterized by a partial activation of type I IFN system and a lack of systemic inflammatory response which may be related to viral persistence. Significance and Impact of the Study: The immune response observed in gilthead seabream infected by LCDV-Sa could be implicated in the establishment of an asymptomatic persistent infection.
Keywords: Inhibidores víricos; asymptomatic infection; gilthead seabream (Sparus aurata); immune gene expression; lymphocystis disease virus; viral challenge